PENGISIAN AIRTANAH BUATAN (ARTIFICIAL RECHARGE) DALAM RANGKA MENGATASI BENCANA BANJIR LONGSOR DAN KETERSEDIAAN AIR TANAH DI KOTA PADANG - Edial, Helfia (Jurnal Spasial, 2015)
Problem of flooding and landslides in Indonesia are already an issue ordinary and natural, is due to geological conditions, geomorphological and meteorological Indonesia is very appropriate, ditambahlagi with the increasing number of population so many changes in land use of natural land into land settlements and land courts work. As a result, the problem of floods and landslides remain overshadow our lives. Several methods of flood and landslide risk reduction that can be done is to increase the capacity of infiltration of rainwater into the ground, therefore naturally infiltration process is reduced, then the artificial infiltration also can be done by methods as follows; Methods of spreading water on the surface "Water spreading", include; Methods basin.  "Basin Method), Method trenches "Furrow method", Method of natural channel "Natural channel method", Method immersion "Flooding method" , method of irrigation (irrigation method), method of replenishment of groundwater through pits, charging method of groundwater through wells injekasi, method "induced recharge". With this method, the risk of flooding and landslides will be reduced and even stopped with the help of other technical methods, in addition to the availability of the amount of groundwater can also be maintained.Keywords; Flood, Infiltration and Groundwater